2023
DOI: 10.1186/s12909-023-04029-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of virtual reality compared to the role-playing methodology in basic life support training: a two-arm pilot community-based randomised trial

Abstract: Introduction Virtual reality (VR) is a technology that allows us to replace our real environment with one created with digital media. This technology is increasingly used in the training of healthcare professionals, and previous studies show that the involvement and motivation of students who participate in activities that use VR increases compared to those who undergo training with the traditional methodology. The main aim of the study is to evaluate the learning curve of the students using a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…80,81 Finally, we saw examples of virtual reality (VR) and augmented reality (AR), newer digital innovations, in substitutional changes to teaching and learning. [82][83][84] One hundred forty-four articles used technology to augment, or add to, the current teaching methods, giving extra opportunities for learning. Technologies used included social media, 51 virtual reality, 85 game-based learning [86][87][88][89] and mobile or web-based activities.…”
Section: Samr Categorisationmentioning
confidence: 99%
See 1 more Smart Citation
“…80,81 Finally, we saw examples of virtual reality (VR) and augmented reality (AR), newer digital innovations, in substitutional changes to teaching and learning. [82][83][84] One hundred forty-four articles used technology to augment, or add to, the current teaching methods, giving extra opportunities for learning. Technologies used included social media, 51 virtual reality, 85 game-based learning [86][87][88][89] and mobile or web-based activities.…”
Section: Samr Categorisationmentioning
confidence: 99%
“…Other areas where substitution took place included the development of electronic Objective Structured Clinical Examinations (eOSCES) 31,32,35,36,79 and learning resources such as ebooks 80,81 . Finally, we saw examples of virtual reality (VR) and augmented reality (AR), newer digital innovations, in substitutional changes to teaching and learning 82–84 …”
Section: Technology‐led Transformations In Hpe: Literature Exploratio...mentioning
confidence: 99%
“…Conversely, in a previous study, third-year undergraduate dental students participated in role play sessions within the classroom and students in virtual media group were allowed to access materials outside the classroom at their discretion and convenience [ 19 ]. Pedrosa et al showed significantly greater scores among trainees in virtual reality compared to role play in basic life support (BLS) training [ 21 ]. This difference is likely due to the self-training strategy in virtual reality compared to traditional role playing simulation among health professionals in BLS training.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Disadvantages of traditional simulation include: high-cost, large space requirement, facilitator expertise requirement, ethical issues in human or animal tissue use, and difficulty in, or high-cost of, repeating the educational experience. 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%